Barriers to Excellence: Unveiling the Challenges in Modern Science Education a Case of Ethiopia's Education System - Goshu, Belay Sitotaw; Weldeamueal, Melaku Masresha; Ridwan, Muhammad (Budapest International Research and Critics University, 2025)
The quality of higher education in Ethiopia faces significant challenges in producing graduates equipped to address real-world problems effectively. While academic institutions focus on theoretical knowledge, there is a growing concern that students are not prepared to tackle societal issues or engage with community needs. This study aims to assess the barriers to effective science education in Ethiopia's higher education system, focusing on how these barriers affect professional competency and ethical responsibility. A mixed-methods approach was employed, including qualitative interviews with educators, employers, and community leaders, and a quantitative survey of graduates. The study examined the gap between theoretical knowledge imparted during training and the practical skills required in the workplace. Key findings reveal that while graduates possess advanced theoretical understanding, they struggle to apply this knowledge ethically and practically to address community issues. The lack of focus on ethics, practical skills, and community engagement in the curriculum is a gap identified. The study concludes that Ethiopian higher education needs a comprehensive reform to integrate ethical training, practical application, and soft skills development into the curriculum. Collaboration between academia, industry, and communities is essential to bridge the gap between theory and practice. In addition, a more dynamic and inclusive education system should aim to create graduates who can ethically contribute to solving real-world problems and fostering sustainable community development.